Association of B7‐H3 expression with racial ancestry, immune cell density, and androgen receptor activation in prostate cancer. Issue 12 (25th March 2022) - Mendes, Adrianna A.; Lu, Jiayun; Kaur, Harsimar B.; Zheng, Siqun L.; Xu, Jianfeng; Hicks, Jessica; Weiner, Adam B.; Schaeffer, Edward M.; Ross, Ashley E.; Balk, Steven P.; Taplin, Mary‐Ellen; Lack, Nathan A.; et al.
Abstract : Background: B7 homolog 3 (B7‐H3) is an immunomodulatory molecule that is highly expressed in prostate cancer (PCa) and belongs to the B7 superfamily, which includes PD‐L1. Immunotherapies (antibodies, antibody‐drug conjugates, and chimeric antigen receptor T cells) targeting B7‐H3 are currently in clinical trials; therefore, elucidating the molecular and immune microenvironment correlates of B7‐H3 expression may help to guide trial design and interpretation. The authors tested the interconnected hypotheses that B7‐H3 expression is associated with genetic racial ancestry, immune cell composition, and androgen receptor signaling in PCa. Methods: An automated, clinical‐grade immunohistochemistry assay was developed by to digitally quantify B7‐H3 protein expression across 2 racially diverse cohorts of primary PCa (1 with previously reported transcriptomic data) and pretreatment and posttreatment PCa tissues from a trial of intensive neoadjuvant hormonal therapy. Results: B7‐H3 protein expression was significantly lower in self‐identified Black patients and was inversely correlated with the percentage African ancestry. This association with race was independent of the significant association of B7‐H3 protein expression with ERG/ETS and PTEN status. B7‐H3 messenger RNA expression, but not B7‐H3 protein expression, was significantly correlated with regulatory (FOXP3‐positive) T‐cell density. Finally, androgen receptor activity scores were significantly correlated with B7‐H3 messenger RNA expression, and neoadjuvant intensive hormonal therapy was associated with a significant decrease in B7‐H3 protein expression. Conclusions: The current data underscore the importance of studying racially and molecularly diverse PCa cohorts in the immunotherapy era. This study is among the first to use genetic ancestry markers to add to the emerging evidence that PCa in men of African ancestry may have a distinct biology associated with B7‐H3 expression. Lay Summary: B7‐H3 is an immunomodulatory molecule that is highly expressed in prostate cancer and is under investigation in clinical trials. The authors determined that B7‐H3 protein expression is inversely correlated with an individual's proportion of African ancestry. The results demonstrate that B7‐H3 messenger RNA expression is correlated with the density of tumor T‐regulatory cells. Finally, in the first paired analysis of B7‐H3 protein expression before and after neoadjuvant intensive hormone therapy, the authors determined that hormone therapy is associated with a decrease in B7‐H3 protein levels, suggesting that androgen signaling may positively regulate B7‐H3 expression. These results may help to guide the design of future clinical trials and to develop biomarkers of response in such trials. Abstract : B7‐H3 protein expression was significantly lower in self‐identified Black patients and was inversely correlated with the percentage African ancestry. Androgen receptor activity scores were significantly correlated with B7‐H3 messenger RNA expression, and neoadjuvant intensive hormonal therapy was associated with a significant decrease in B7‐H3 protein expression, consistent with a presumed androgen receptor binding site upstream of the B7‐H3 promoter.